2013
DOI: 10.1186/1471-2105-14-s5-s15
|View full text |Cite
|
Sign up to set email alerts
|

A novel min-cost flow method for estimating transcript expression with RNA-Seq

Abstract: BackgroundThrough transcription and alternative splicing, a gene can be transcribed into different RNA sequences (isoforms), depending on the individual, on the tissue the cell is in, or in response to some stimuli. Recent RNA-Seq technology allows for new high-throughput ways for isoform identification and quantification based on short reads, and various methods have been put forward for this non-trivial problem.ResultsIn this paper we propose a novel radically different method based on minimum-cost network f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 22 publications
0
99
0
Order By: Relevance
“…Note that if more than a certain percentage of the reads (by default 95%) aligned in a gene locus are multi-mapped, then StringTie will skip processing that locus. The ASG captures all possible transcripts that are consistent with the mapped reads 15,17 , where nodes in the graph correspond to contiguous regions of the genome that are uninterrupted by any spliced read alignment, and directed edges correspond to reads that align across two such nodes in the correct 5′ to 3′ order. Note that the nodes do not necessarily correspond to whole exons in the transcripts; they may be only partial exons, as illustrated by node 4 in Supplementary Figure 12 (see also node 1 in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that if more than a certain percentage of the reads (by default 95%) aligned in a gene locus are multi-mapped, then StringTie will skip processing that locus. The ASG captures all possible transcripts that are consistent with the mapped reads 15,17 , where nodes in the graph correspond to contiguous regions of the genome that are uninterrupted by any spliced read alignment, and directed edges correspond to reads that align across two such nodes in the correct 5′ to 3′ order. Note that the nodes do not necessarily correspond to whole exons in the transcripts; they may be only partial exons, as illustrated by node 4 in Supplementary Figure 12 (see also node 1 in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although a growing number of methods have been developed to solve either the transcript identification problem (e.g., Trinity 7 , Oases 8 ), the expression quantification problem (e.g., RSEM 9 , eXpress 10 ) or both (e.g., IsoInfer 11 , Scripture 12 , Cufflinks 13 , SLIDE 14 , IsoLasso 15 , iReckon 16 , Traph 17 ), much work remains to produce consistent, highly accurate solutions. A recent study 18 of the current transcript reconstruction methods showed that even in cases where these methods identified all constituent exons of a transcript, they often failed to assemble the exons into complete isoforms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the challenges that have to be dealt with in viral quasispecies assembly can also be found in RNA transcipt assembly, where the goal is to reconstruct an unknown number of transcripts and predict the relative transcript abundances. Not surprisingly, many RNA transcipt assemblers define graph optimization problems similar to our flow formulation [21,22,23,24,25]. Although dealing with related problems, these methods cannot be applied in a viral quasispecies setting so easily: they require a collection of reference genomes representing all possible haplotypes as input, which is not available in our setting.…”
Section: Introductionmentioning
confidence: 99%